Skrining fitokimia dan uji aktivitas antiinflamasi ekstrak akar Sonneratia alba terhadap luka bakar pada tikus (Rattus norvegicus): Indonesia - Mongi, Jeane; Karauwan, Ferdy A.; Tuda, Aletheia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Burns caused by inflammation can lead to severe and potentially fatal conditions, especially if the burn is located in a very sensitive area of the body or if the burn becomes infected. Untreated inflammation can cause very severe inflammation, which can damage cells, tissues, or organs. The roots of Sonneratia alba contain alkaloids, flavonoids, saponins, triterpenoids, and tannins that can help heal burns. The aim of this research is to determine the phytochemistry and the effects of the ethanolic extract of Sonneratia alba roots on the healing of burn wounds on rat skin. Research Method: The research uses an experimental method. The research includes the extraction stage, using 96% ethanol as a solvent in the maceration process, and the ethanol extract of S. alba roots is screened for its chemical content. Testing phase of the anti-inflammatory activity of Sonneratia alba mangrove root extract on burn wound healing. Experimental animals used were 15 Rattus norvegicus rats divided into 5 groups with different concentrations of 3 treatments, that is: the positive control group with Bioplacenton gel, the negative control group with Aquadest, the group with 15% ethanol extract of S. alba root, the group with 30% ethanol extract of S. alba root, and the group with 45% ethanol extract of S. alba root. During the observation phase, the measurement of burn healing diameter was conducted over 32 days using callipers. The research result show that the ethanol extract of Sonneratia alba roots contains alkaloids, flavonoids, saponins, tannins, triterpenoids, and phenolic compounds. The 15%, 30%, and 45% concentrations of the ethanol extract of Sonneratia alba roots have the potential to heal burns in rats. Ethanolic root extract showed an increase in healing power after the 20th day, faster than Biopalcenton gel.